City under one roof (Berkley, 2023)
"A stranded detective tries to solve a murder in a tiny Alaskan town where everyone winters in the same high-rise building, in this gripping debut by Academy Award-nominated screenwriter Iris Yamashita. When a local teenager discovers a severed hand and foot washed up on the shore of the small town of Point Mettier, Alaska, Cara Kennedy is on the case. A detective from Anchorage, she has her own reasons for investigating the possible murder in this isolated place, which can be accessed only by a tunnel. After an avalanche causes the tunnel to close indefinitely, Cara is stuck among the odd and suspicious residents of the town--all 205 of whom live in the same high-rise building and are as icy as the weather. Cara teams up with Point Mettier police officer Joe Barkowski, but before long the investigation is upended by a gang from a nearby reservation who are seeking shelter from the snowstorm. Cara soon discovers that everyone in this town is keeping secrets. If there is anything as elusive as the residents themselves, it's answers"--

Restless in the grave (Kate Shugak, ,, 2012)
New York Times bestseller Dana Stabenow returns with her most outstanding novel yet, teaming up two of her most beloved characters, Aleut private investigator Kate Shugak and Alaska state trooper Liam Campbell, in the same story for the first time. Alaska aviation entrepreneur Finn Grant died in the fiery crash of his Piper Super Cub. Someone sabotaged his engine, and virtually everyone in southwestern Alaska has a motive, including his betrayed wife, his bullied children, and Liam's wife, bush pilot Wyanet Chouinard. With few places to turn, Liam asks his former mentor Niniltna post commander Sergeant Jim Chopin, for help, and Jim quickly brings Kate onto the case. Working undercover as—of all things—a waitress at Bill's Bar and Grill, Kate learns over beer and burgers that Grant's business had expanded meteorically over the last two years. After buying the closed Air Force base south of town from the federal government at a bargain-basement price, he became a fixed-base operator running his fishing, hunting, and flight-seeing business, servicing planes flying through the area, and most interestingly and lucratively, getting into the air freight business. But what kind of freight was he moving, and where? The answers involve Kate in her most challenging case to date, one that starts with murder and quickly sprawls into a much larger conspiracy ranging from the darkest family secrets to treason and beyond. Restless in the Grave is a treat for fans and another outstanding addition to Dana Stabenow's acclaimed and award-winning series.

Northern lights (G. P. Putnam's Sons, Brilliance Audio, 2004)
Seeking to rebuild his life, ex-Baltimore cop Nate Burke takes a job as Chief of Police in the tiny, remote Alaskan town of Lunacy, where he comes face to face with the independent Meg Galloway and an unsolved fifteen-year-old-crime.

Death takes passage: an Alaska mystery (Avon, 1998)
Description Not Provided

Deadfall: an Alaska mystery (Avon Twilight, 1999)
Description Not Provided

So sure of death: a Liam Campbell mystery (Dutton, 1999)
Alaska state trooper Liam Campbell must use his knowledge of native ways to solve two crimes. In one, an archeologist is murdered, in another, seven people die in a boat fire, the work of an arsonist.

Spoils of the dead: a Liam Campbell novel (Liam Campbell, 5,, 2021)
Restationed in a remote bush town in the aftermath of a fatal judgment call, Trooper Liam Campbell tackles unexpected challenges in the form of a cutthroat local fishing trade, violent drug dealers, and the murder of an archaeologist who claimed to be on the verge of a great discovery.